Pengembangan Media Pembelajaran Kalkulator LEGO untuk Meningkatkan Pemahaman Konsep Perkalian Siswa MI Plus Ar-Ridha - Nadia Salsabila; Lailatun Nur Kamalia Siregar (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
This study aims to develop LEGO Calculator learning media based on the ADDIE model to support third-grade students’ conceptual understanding of multiplication at MI Plus Ar-Ridha. The novelty of this study lies in the design of LEGO blocks as a concrete calculator that represents multiplication through vertical and horizontal block arrangements, allowing students to connect repeated addition, grouped quantities, and symbolic multiplication. Unlike general manipulative media that mainly function as counting aids, the LEGO Calculator integrates constructive play, concrete representation, collaborative learning, and Wordwall-assisted interactive questions in one learning sequence. This study employed a Research and Development method using the ADDIE model and involved 21 third-grade students of MI Plus Ar-Ridha. Data were collected through observation, interviews, expert validation sheets, teacher and student response questionnaires, and pretest-posttest instruments. The instruments were reviewed through expert judgment to ensure content suitability, language clarity, readability, and alignment with multiplication concept indicators. The data were analyzed using descriptive quantitative analysis and N-Gain calculation. The results showed that the media was highly feasible, with an average score of 4.6 from the media expert and 4.5 from the material expert. The practicality test obtained 92% from the teacher response and 90.4% from student responses. The limited trial showed an increase in the average score from 58.1 in the pretest to 89.5 in the posttest, with an N-Gain score of 0.8 in the high category. These findings indicate that the LEGO Calculator can serve as an alternative manipulative medium to support concrete, interactive, and meaningful multiplication learning in elementary mathematics.